Comparison of Online Learning Effectiveness in the Ele During Covid-19 in Malaysia and Indonesia - Tiyas Saputri; Aslam Khan Bin Samahs Khan; Mohammad Abdul Kafi (Pioneer: Journal of Language and Literature, 2020)
The Covid-19 pandemic has an impact on education. It has changed the learning system, from conventional interaction into digital interaction. The lecturers and students in Malaysia and Indonesia are required to master online learning to conduct the teaching and learning processes. However, not many lecturers apply it maximally. This study aims to find out the comparison of online learning effectiveness in English Language Education (ELE) in Malaysia and in Indonesia. This quantitative research used a questionnaire survey to collect data. The data were analyzed descriptively with tabulations and distributions of empirical data. The result reveals that 75% of Malaysian lecturers and 83% of Indonesian lecturers prefer to use synchronous learning; 25% of Malaysian lecturers and 17% of Indonesian lecturers prefer to use asynchronous learning; 65% of Malaysian students and 71% of Indonesian students prefer to use synchronous learning; 35% of Malaysian students and 29% of Indonesian students prefer to use asynchronous learning. For synchronous learning, 58% of the total respondents in Malaysia like virtual meeting as an online learning tool. In Indonesia, 59% of the total respondents like phone call as an online learning tool. For asynchronous learning, 54% of the total respondents in Malaysia and Indonesia like blog as an online learning tool. Online learning has good effects on the English learning skills, especially listening. Academics in both countries agree that online learning is beneficial in the ELE learning and teaching process. It can be generally concluded that the use of online learning and teaching is effective in ELE.